ANALISA PERBANDINGAN STRUKTUR BAJA 3 LANTAI MENGGUNAKAN SYSTEM CBF DAN EBF DENGAN METODE PUSH OVER ANALYSIS - Sumaidi Sumaidi; Wahyu Kartini; Anna Rumintang (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
Indonesia is a country that is in the ring of fire and on several tectonic plate boundaries. so the risk level of an earthquake is very high. The structural analysis used is a comparison of concentrically braced frames (CBF) and eccentrically braced frames (EBF) systems based on earthquake resistant structure regulations. The analysis result shows that the structure ductility with CBF system is smaller than the EBF system. The structure with the CBF system is more rigid and sturdier than the EBF system. Good ductility is more than 1, so the structure does not collapse easily. In linear conditions, CBF systems have better behavior or performance as indicated by the use of materials, maximum displacement and smaller drift ratios. In nonlinear conditions, this system (EBF) has better behavior and performance as evidenced by better energy absorption and ductility.